HUBUNGAN POWER OTOT TUNGKAI DENGAN HASIL SMASH KEDENG PADA ATLET SEPAKTAKRAW PUTRA PPLP RIAU - Tabrani, Tabrani; Saripin, Saripin; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : Based on the information obtained from the PPLP Riau training, the tight smash of athletes sepaktakraw PPLP that there is now not showing the maximum of smash kedeng. This can be seen from the smasher often fails to smash kedeng with hard and sharp, besides that smash is often inaccurate and the ball is often out at the time of smash. The purpose of this research is to know the correlation between leg muscle power with the result of smash kedeng man athlete sepaktakraw PPLP Riau. The population in this research man is athletes sepaktakraw PPLP Riau, amounting to 12 people. Sampling in this research using total sampling technique, so the sample in this study amounted to 12 people. The instrument used to collect data is the leg muscle power test using vertical power jump test and the smash test can be measured with the ability to test smash kedeng. Data Analyzed technique using correlation of momet product. Based on the results of research that has been authors described in the previous chapter, it can be concluded that the results obtained leg muscle power has a relationship with the results of kedeng smash on athletes sepaktakraw man PPLP Riau, this is seen from the results of analysis stating that the results r arithmetic (0.679 )> r table (0.602).Keywords : Limb Muscle Power, Kedeng Smash